Theoretical Investigation on Thermal, Mechanical and Ultrasonic Properties of Zirconium Metal with Pressure - Srivastav, P.; Prajapati, A.K.; Yadawa, P.K. (Physics and Chemistry of Solid State, 2023)
Zirconium (Zr), a metal with an hcp structure, has been investigated for the transmission of acoustic wave in the 0 to 25 GPa operating pressure. For this, the Lennard-Jones interaction potential approach has been used to estimate the higher order elastic coefficients (SOECs and TOECs). This model is used to calculate the 2nd and 3rd order elastic parameters for zirconium metal. With the help of SOECs, other elastic moduli such as bulk modulus (B), Young’s modulus (Y) and shear modulus (G) have been calculated for Zr metal using Voigt-Reuss-Hill (VRH) approximations. Later, applying SOECs as well as zirconium density under the same pressure range, three orientation dependent acoustic velocities, comprising Debye average velocities, have been studied. Basic thermal characteristics such as specific heat at constant volume, thermal conductivity associated with lattice, thermal energy density, thermal relaxation time as well as acoustic coupling coefficients of zirconium metal have been also calculated at same pressure range. The computation is also satisfactory in estimating the ultrasonic attenuation coefficients, arises due to the interaction of phonons, hardness as well as melting temperature under various pressures in this research work.